Functionality of Native Starches in Food Systems: Cluster Analysis Grouping of Rheological Properties in Different Product Matrices - Le Thanh-Blicharz, Joanna (Foods, 2020)
Industrial application of starch as a texture-forming agent is primarily limited to preparations obtained from waxy corn and potatoes. The main reason behind this is its functionality, which depends mostly on rheological properties. However, in food product matrices, these properties change. Despite the vast amount of information on the rheological properties of various starches, the rational choice of thickener appears to be an extremely difficult task. The aim of the work is to systemize the information on the rheological properties of most popular starches in matrices of various food products, applying principal component and cluster analyses. The investigated material is potato and corn starch of the normal and waxy varieties. Binary mixtures containing salts or sweetening agents, as well as four different food products (ketchup, mayonnaise, pudding, and jelly), are investigated. It was found that compared to normal varieties, waxy starches reveal many similar rheological properties in all investigated models and food systems. Furthermore, in most applications, one waxy starch variety may be substituted by another, with no significant impact on the rheological properties and texture of the food product. Moreover, waxy starch preparations are less altered by the presence of cosolutes, i.e., salts and sugar alcohols. Starch model systems were proven to be useful only for rapid thickener screening tests and cannot be recommended as a final reference for the quality design of food products.